High-Speed Digital Detector for the Internet of Things Assisted by Signal’s Intensity Quantification - Zhang, Yidi; Wang, Haibo (Frontiers in Physics, 2021)
This paper proposes a high-speed digital detector for the Internet of Things (IoT) assisted by signal's intensity quantification. The detector quantifies the amplitude of each pixel of the detected image and converts it into a digital signal, which can be directly applied to the IoT with wireless communication system. Two types of amplitude quantization algorithms, uniform quantization and non-uniform quantization, are applied to the detector, which further improves the quality of the detected image and the robustness of the image signal in a noisy environment. Related simulations have been established to verify the accuracy of the models and algorithms.